Palladium-Catalyzed Carbonylative Cross-Coupling Reaction between Aryl(Heteroaryl) Iodides and Tricyclopropylbismuth: Expedient Access to Aryl Cyclopropylketones - Benoit, Emeline; Dansereau, Julien; Gagnon, Alexandre (Synlett, 2017)
The carbonylative cross-coupling reaction between aryl and heteroaryl iodides and tricyclopropylbismuth is reported. The reaction is catalyzed by (SIPr)Pd(allyl)Cl, a NHC-palladium(II) catalyst, operates under 1 atm of carbon monoxide and tolerates a wide range of functional groups. The use of lithium chloride was found to provide higher yields of the desired aryl cyclopropylketones. The conditions were also applied to the carbonylative cross-coupling of an iodoalkene to afford the corresponding alkenyl cyclopropylketone.
Keywords: aryl cyclopropylketones; carbon monoxide; carbonylative cross-coupling; NHC ligand; palladium; tricyclopropylbismuth